Peran Kedisiplinan, Kompetensi Dan Komunikasi Terhadap Kinerja Pegawai Melalui Motivasi Kerja (Studi Pada Dinas Sosial Tenaga Kerja Dan Transmigrasi Kota Yogyakarta) - Dwi Hartati; Etty Indriani (STIE AUB Surakarta, 2025)
Quantitative research aims to determine, test and analyze empirically the influence of discipline, competence and communication on work motivation and employee performance at the Yogyakarta City Social Workforce and Transmigration Service. Research data uses primary data from respondents regarding questionnaire answers. Sampling using census techniques was 75 respondents. Data analysis uses path analysis, hypothesis testing, direct, indirect and total effects. The research results show that competence and communication have a positive and significant effect on work motivation, while discipline has a positive and insignificant effect on work motivation; communication has a positive and significant effect on performance, while discipline, competence and work motivation has a positive and insignificant effect on performance. The results of the F test show that discipline, competence and communication on work motivation have a significant effect on performance. The total R square value of 0.955 means that performance is explained by discipline, competence, communication and work motivation by 95.5% and the remaining 4.5% is explained by other factors outside the research model, for example work environment variables, organizational culture and so on. . The results of the path analysis show that the direct path of communication to performance is the most dominant and most effective path for improving performance. The results of the Sobel test show that work motivation is unable to mediate the relationship between discipline, competence and communication on performance.